Pengaruh Media Geo Lane terhadap Kemampuan Mengenal Bentuk Geometri Anak Usia 4-5 Tahun Di TK Taqwa Al-Hidayah Danto Kabupaten Kampar - Arva Mustika Anggraini; Zulkifli Zulkifli; Enda Puspitasari (Journal on Education, 2023)
The use of learning media is considered very appropriate and effective to be applied to early childhood. One of the learning media that can help children get to know geometric shapes is geo lane media. This study aims to determine the influence of geo lane media on the ability to recognize geometric shapes of children aged 4-5 years at Taqwa Al Hidayah Danto Kindergarten. The type of research used is experimental quantitative research with the research design One Group Pretest-Posttest Design with a total sample of 15 children. The data collection technique used in this study was to use an observation sheet to recognize geometric shapes. The data analysis technique uses a t-test using the SPSS ver 23 program. The results showed that there were differences in the ability to recognize geometric shapes before and after using geo lane media. Judging from the average number before using geo lane media is an average of 44% and the average value afterwards is 98%. Based on the t-test using the Paired Sample Test, the results of the calculated t test = 11,525 with Sig = 0.000 were obtained. Since the value of Sig < 0.05, means significant. It can be concluded that sig (2-tiled) 0.000 < 0.05. This means that there is a significant influence of geo lane media on the ability to recognize geometric shapes of children aged 4-5 years between before and after using geo lane media.